Namāẓij Ta’līm an-Naḥwi fī Ma’had Nūr al-Qur’ān litaḥfīẓ al-Qur’ān Magelang Jāwā al-Wusṭā - Sri Guno Najib Chaqoqo; Ahmad Rafiq (IAIN Salatiga, 2022)
This article focused on studying the dynamic nahwu learning curriculum developed by Nurul Qur'an Islamic Boarding School for Tahfidz (PPNQ) Jumoyo Salam, Magelang, Central Java. It aimed at describing nahwu learning in the pesantren, focusing on memorizing the Qur'an. The method used was participatory, done by being directly involved in the learning at PPNQ, starting from the design of learning, students placement, building classes, and deciding the books used. Data were collected through observation, limited discussion, and interviews with the teachers, students, and administrators. The study found that the learning dynamics are developed in this pesantren because the curriculum is not yet stable. The dynamics are in the form of students' obligation to present on each subject (book) taught and to memorize at another time. The fact is different from the eras before this dynamic development. It is very interesting considering that the Islamic Boarding School for Tahfidz is known as a pesantren that firmly adheres to the principle of maintaining a tradition that has been going on for decades. Therefore, dynamic observations are also needed regarding subsequent developments.